(untitled) (Semiárida, 2020)
The objective of this work was to determine the optimum plant density of squash type Butternut (Cucurbita moschata) in the semiarid region of La Pampa. The test was carried out in the Anguil INTA experimental station. In this experiment Cuyano INTA was used in three densities: 10.000 plants.ha-1, 6.666 plants.ha-1 and 5.000 plants.ha-1. The crop was planted on 26/11/09 and harvested on 25/03/10. The experimental design was randomized blocks with 4 repetitions, where each plot included 10 plants. The experiment evaluated yield, fruit weight and number of each plant. Statistical analysis using ANOVA and Duncan test 5% were performed on the data. The results did not show differences between densities in total and commercial yield per hectare and percentage of waste. The total and commercial yield by plant was higher in lower density. The average weight of commercial fruit was higher at the lower density. Different planting densities did not result in significant differences in total and commercial yield per hectare. Increasing the density of plants decreased the size of commercial fruit and the number of fruit per plant.